THE TRADITIONAL FAMILY, IN THE ROLE OF THE FUNDAMENTAL MATRIX OF THE FORMATION OF INDIVIDUAL CONSCIOUSNESS – A RADIOGRAPHY AT THE LEVEL OF THE ROMANIAN SOCIETY - Mirela Cristiana NILĂ STRATONE; Bogdan MARINESCU (Challenges of the Knowledge Society)
The primary group, accepted at all times as the core of society, is subject to a continuous assault. The reason invoked is so-called change, novelty, elements that only open-minded can accept. The main problem that arises in this approach is that the open mind does not mean the mind that accepts any element of novelty, but the mind that analyzes and selects. Between the acceptance of everything and the selection, it is desired to merge these two elements till total confusion. But who wants to create this confusion and why? The answer to this question is actually the quintessence of the present study. First of all, we need to make it clear that the traditional family has an important contribution to clarifying this issue. Of course, in terms of family and open-mind, we must admit that the time has come to make the difference between the modern family and the traditional family. Another determining element which creates this confusion is represented by the mass media. Regardless of the type of communication channel, interest groups have not bypassed the opportunity of communication channel to reach their objectives through manipulation in the public sphere over time. Along with the family and the media, with an influence that does not necessarily occupy the last place after the two social factors, we have to take in consideration the church. Of course, we need to make some clarifications at this point: firstly, the difference between the church as an institution, religion and faith, and second, the difference between the dominant religious beliefs in society. However, it should be noted that the church institution accepts only one way of family existence, namely the traditional one. Along with this, the church emphasizes the conservative elements of social and individual culture, guiding the individual on the analytical and selective sphere, which predominantly leads to the positive segment of social values. Our study aims to highlight the role of the traditional family in the process of building the matrix on which individual consciousness is developed and, in the course of time, in an area comprised of territorial and cultural borders, national consciousness. Interesting is the barrier that emerged between the Romanian traditional consciousness and the diversified novelty wave, the barrier materialized in an increasingly visible resistance both in material and virtual way in accepting the modern type of family to the detriment of the traditional one.